VHDL modeling of optimum measurement selection by using genetic algorithm - Ullah, Mohammad Habib; Hasan, Muhammad Asfarul; Uddin, Md. Jasim; Priantoro, Akhmad Unggul (INSI Publications, 2009)
A Genetic Algorithm (GA) that is going to be a part of a system for obtaining optimum sensor measurements for a specific process. Most parts in the design accomplished using Very High Speed Integrated Circuit Hardware Description Language (VHDL), then simulated and verified using Design Architect (DA) and ModelSim CAD tools. This paper consists of the design of a Multiplier based on an unsigned shift and adds procedure, and a Divider based on the Fixed-point shift and subtract method, specifically for this task. It is designed in a way that it can be mapped into an Integrated Circuit (IC). Some issues in the design need some further consideration. The purpose of this research is to come up with hardware based Genetic Algorithm that is used in Optimum Measurement Selection.